SOSIALISASI PERENCANAAN PAGAR LINGKUNGAN DI KELURAHAN BENDUNG, KECAMATAN KASEMEN, KOTA SERANG - Darmawan Pontan; Martinus Bambang Susetyarto; Heru Pambudi (Yayasan Education and Social Center, 2022)
Planning an environmental fence in Kelurahan Bendung, Kecamatan Kasemen, Kota Serang, Province of Banten is a preventive effort in the development of the village area in order to create a safe and comfortable atmosphere for the community. This effort is supported by the Community Service Team, Faculty of Civil Engineering and Planning, Universitas Trisakti, in the form of socialization activities for environmental fence planning to officials and residents of Kelurahan Bendung. The activity was preceded by the initial activity of Situation Analysis and Prioritization of Partner Problems, namely the residents of Kelurahan Bendung. The team coordinated with the officials of Kelurahan Bendung, as well as informal community leaders, discussed intensively to decide on the best agreed solution to be resolved together. The focus of the activity is the socialization of environmental fence planning with the BRC building materials. The service method is the S curve method with five steps, namely preparation, socialization, evaluation, report, and output. The idea of ??community service activities is associated with plans for the development of public facilities and infrastructure in the coming fiscal year. The socialization materials included an understanding of environmental fences, building materials used, and preparation of Working Drawings, Technical Specifications, Budget and Cost Plans for the pilot project, namely the physical construction of the BRC fence in Kelurahan Bendung. Therefore, the contents of the socialization materials need to be well prepared, including the method of measuring the empowerment experienced by the socialization participants in this pandemic situation. Meanwhile, a literature study was conducted so that in compiling the socialization materials references to building materials and technology, project financing management and construction techniques of BRC steel fences were carried out. Hopefully the knowledge of socialization of environmental fence planning can be useful for the community of Kelurahan Bendung